2018
DOI: 10.1371/journal.pgen.1007662
|View full text |Cite
|
Sign up to set email alerts
|

Rice transcription factor OsMADS25 modulates root growth and confers salinity tolerance via the ABA–mediated regulatory pathway and ROS scavenging

Abstract: Plant roots are constantly exposed to a variety of abiotic stresses, and high salinity is one of the major limiting conditions that impose constraints on plant growth. In this study, we describe that OsMADS25 is required for the root growth as well as salinity tolerance, via maintaining ROS homeostasis in rice (Oryza sativa). Overexpression of OsMADS25 remarkably enhanced the primary root (PR) length and lateral root (LR) density, whereas RNAi silence of this gene reduced PR elongation significantly, with alte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
98
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(114 citation statements)
references
References 89 publications
(107 reference statements)
5
98
0
Order By: Relevance
“…These findings indicated that promoting root growth improves tolerance to abiotic stress and rice productivity. This finding is supported by studies using OsMADS25 that regulates root elongation and formation in rice by controlling the auxin response [82,98]. In this study, the knock-down mutant of OsMADS25 with reduced root growth exhibited high sensitivity to salinity and oxidative stress, while transgenic rice overexpressing OsMADS25 displayed enhanced tolerance to the abiotic stress [98].…”
Section: Root Development and Stress Tolerance In Ricesupporting
confidence: 60%
“…These findings indicated that promoting root growth improves tolerance to abiotic stress and rice productivity. This finding is supported by studies using OsMADS25 that regulates root elongation and formation in rice by controlling the auxin response [82,98]. In this study, the knock-down mutant of OsMADS25 with reduced root growth exhibited high sensitivity to salinity and oxidative stress, while transgenic rice overexpressing OsMADS25 displayed enhanced tolerance to the abiotic stress [98].…”
Section: Root Development and Stress Tolerance In Ricesupporting
confidence: 60%
“…a). This diversity of expression patterns and putative functions adds to the complex evolution of AGL17 ‐like genes, as genes from this subfamily have been implicated in various different functions, including root development, flowering time control, tillering, stomata development and stress response (Kutter et al ., ; Guo et al ., ; Puig et al ., ; Hu et al ., ; Xu et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Remarkably, genes of these expanded clades do control traits that are important for adaptation to different environments. For example, AGL17 ‐like genes are involved in root development and stress response and FLC ‐like genes determine flowering time (Xu & Chong, ; Xu et al ., ). On the other hand, smaller MIKC‐type subclades involved in highly conserved developmental functions, such as AP3/PI ‐ or AG/STK ‐like genes, which control reproductive organ identity (Theißen et al ., ), tend to be located more in central chromosomal segments (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…OsMAD25 and 27 exert an inhibitory effect on primary root development, but they promote the elongation of LRs in an auxin-dependent manner ( Yu et al , 2015 ; Chen et al , 2018 ; Zhang et al , 2018 ). Additionally, the overexpression of OsMAD25 and 27 enhances salinity tolerance in rice via modulation of the ABA signaling pathway ( Chen et al , 2018 ; Xu et al , 2018 ). The monocot-specific miR444 affects post-transcription inhibition of OsMADS genes, because overexpression of OsmiR444 reduced the accumulation of OsMADS23 , 27 , and 57 which in turn decreased LR elongation in a nitrate-dependent manner ( Yan et al , 2014 ).…”
Section: Regulation Of Lateral Roots and Root Hair Development By A Nmentioning
confidence: 99%